Myricetin protects against H2O2‐induced oxidative damage and apoptosis in bovine mammary epithelial cells. Issue 4 (3rd September 2020) - Kan, Xingchi; Liu, Juxiong; Chen, Yingsheng; Guo, Wenjin; Xu, Dianwen; Cheng, Ji; Cao, Yu; Yang, Zhanqing; Fu, Shoupeng
Abstract: High‐producing dairy cows are prone to oxidative stress due to their high secretion and strong metabolism, and excessive oxidative stress may cause the apoptosis of bovine mammary epithelial cells (bMECs). Myricetin (Myr) has been shown to have a wide range of pharmaceutical activities. The aim of this study was to evaluate the effect of Myr on hydrogen peroxide (H2 O2 )‐induced oxidative stress and apoptosis in bMECs and to clarify the underlying mechanism. bMECs were pretreated with or without Myr and then stimulated with H2 O2 . The results showed that Myr significantly increased the total antioxidant capacity and superoxide dismutase levels and decreased the malondialdehyde (MDA) and reactive oxygen species (ROS) levels in a model of oxidative stress induced by H2 O2 in bMECs. Mechanistic studies found that Myr inhibited H2 O2 ‐induced oxidative stress in bMECs through the adenosine monophosphate‐activated protein kinase/nuclear factor erythroid‐2 related factor 2 (AMPK/NRF2) signaling pathway. Additional research found that Myr could also inhibit H2 O2 ‐induced apoptosis in bMECs through NRF2. These data suggest that Myr effectively alleviated oxidative stress and apoptosis in H2 O2 ‐induced bMECs through the activation of the AMPK/NRF2 signaling pathway. Abstract : Hydrogen peroxide (H2 O2 ) inhibited the activity of adenosine monophosphate‐activated protein kinase/nuclear factor erythroid‐2 related factor 2 (AMPK/NRF2) signaling and promoted the release of reactive oxygen species in bovine mammary epithelial cells, which induced oxidative stress, damage mitochondria, and cause apoptosis. Myricetin administration significantly alleviated H2 O2 ‐induced oxidative stress and the apoptosis response by activating AMPK/NRF2 signaling.